Global Graft Sdn. Bhd. / Wan Sulsilawati Sulong, Noor Azila Mohamad @ Khalid and Norhaizey Issia - Sulong, Wan Sulsilawati; Mohamad @ Khalid, Noor Azila; Issia, Norhaizey (Faculty of Applied Sciences, 2005)
The administration is one of the main parts of business plan. The achievement of the business generally depends on the effectiveness of administration. EfFective management will produce a systematic and efficient kind of attitude among the employees. It automatically will increase their working rate.